(untitled) - David Burnley (London, 1992)
This book is divided into five sections covering the main phases in the development of English.Each section includes an introduction outlining the principal themes and issues against which the succeeding passages can be explored
Keywords: english language - dialects - texts,english language - earle modern, 1500-1700 - texts,english language - history - sources,english language - middle english - 1100-1500 - texts,english language - old english, ca. 450-110 - texts